Penetrating injury to the neck - Three case reports with review of literatures - Aich, ML; Alam, ABMK; Abdullah, M; Sardar, AR (Bangladesh Medical Journal, 2014)
Penetrating neck wounds are potentially dangerous and require emergency management because of the presence of vital structures in the neck. Organic foreign bodies further carry a risk of wound infection. Three interesting penetrating neck injury with foreign bodies are presented of which two are metallic, one with bamboo stick penetrating the neck tissue without damaging any vital structures except facial nerve injury. Mod e of entry, the peculiarity of the foreign body, the management protocol and the outcomes of neck injury are evaluated in the three cases of this case report. Review of literature revealed that few such cases have been reported. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18978 Bangladesh Med J. 2013 Jan; 42 (1): 31-33